Measurement of the top-quark mass in tt¯ + 1-jet events collected with the ATLAS detector in pp collisions at √s = 8 TeV - Alonso, Francisco (2019)
A determination of the top-quark mass is presented using 20.2 fb⁻¹ of 8 TeV proton-proton collision data produced by the Large Hadron Collider and collected by the ATLAS experiment. The normalised differential cross section of top-quark pair production in association with an energetic jet is measured in the lepton+jets final state and unfolded to parton and particle levels. The unfolded distribution at parton level can be described using next-to-leading-order QCD predictions in terms of either the top-quark pole mass or the running mass as defined in the (modified) minimal subtraction scheme. A comparison between the experimental distribution and the theoretical prediction allows the top-quark mass to be extracted in the two schemes. The value obtained for the pole-mass scheme is: mpolet = 171.1 ± 0.4 (stat) ± 0.9 (syst) +0.7 −0.3 (theo) GeV. The extracted value in the running-mass scheme is: mt(mt) = 162.9 ± 0.5 (stat) ± 1.0 (syst) +2.1 −1.2 (theo) GeV. The results for the top-quark mass using the two schemes are consistent, when translated from one scheme to the other.